Analysis of Maqashid Syariah Principles in the Governance of Fundraising Activities of Zakat Management Institutions - Moh Khoirul Anam; Risdianto .; Hairullfazli Bin Mohammad Som (IAIN Padangsidimpuan, 2023)
The ability of zakat institutions to collect zakat funds is still far from the existing potential. The collection of national zakat funds reaches Rp. 11.5 trillion to Rp. 233 trillion from the existing potential, or the funds that have been obtained are 5% of the existing potential. This percentage is still very small, so the development of fundraising needs to be continuously developed and solutions need to be found for existing problems. There is no doubt that the zakat institution is the main driving force behind the collection and distribution of zakat funds, the management development of zakat institutions is important. The problems faced by the management of zakat institutions need to be broken down and solutions sought. This study aims to explore solutions to these problems. This study uses field studies by collecting data through interviews and field observations. The results of the study show that management has a vital role in collecting and distributing zakat funds. The application of maqashid sharia principles in management has a significant impact on the development of the Institution. Which is indicated by several benefits obtained by stakeholders, namely muzaki, mustahik and the environment